The Legislative System of the Governorates Councils Low in Iraq - صعب ناجي عبود; وفاء عبد الفتاح عواد (Journal of Madenat Alelem University College, 2009)
It is appeared from the foregoing research that there was a lot of legislations that treated the subject of governorates law, which is not a recent law but it has passed through many stages and the basic goal from its legislating was to give the governorates councils some of the authorities and jurisdictions to take its vital role in presenting the best services for the public. Thus, for the purpose of fulfilling the aim of this law we must take into consideration the legal aspects when legislating it. Also the confusion between the arrangement of the draft law of the governorates councils that are not connected to a region and the modification procedures of the order (17) for (2004) must be removed, because legislating the governorates law will lead to the cancellation of the previously mentioned order, so there is no need for making such modifications now but they will be taken into consideration in the new law.